Grand Desain Pendidikan Perspektif Hadis Nabi SAW - Ngatipan Ngatipan (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Education cannot be achieved without a definite direction that has been previously determined. Hadith as the second source of law in Islamic law has established standard guidelines on philosophical and incidental goals for humans to be able to achieve the highest degree of identity before Allah SWT. With the library research method. This study attempts to examine the goals of Islamic education according to the perspective of the hadith of the Prophet SAW.,. From the results of the discussion, it can be concluded that the goals of Islamic education consist of 2 basic things, namely philosophical goals; so that humans can better recognize their true identity, in other words so that they are truly able to become caliphs on earth and incidental goals; to be able to increase motor, emotional, intellectual and spiritual intelligence which is marked by physical and spiritual maturity.